2019
DOI: 10.1002/jcla.23115
|View full text |Cite
|
Sign up to set email alerts
|

Effect of ketamine combined with lidocaine in pediatric anesthesia

Abstract: Background:We conducted a randomized clinical trial to determine whether adjunctive lidocaine diminishes the incidence of adverse effects in pediatric patients sedated with ketamine. Methods:This case-control study involved 586 consecutive pediatric patients necessitating anesthesia. Then systolic blood pressure, heart rate, respiratory rate, and blood oxygen saturation were observed. Alanine aminotransferase (ALT), aspartate aminotransferase (AST), urea nitrogen (BUN), and creatinine (Cr) levels were tested.G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…In a retrospective analysis of data, in a limited number of pediatric patients undergoing general anesthesia for laparoscopic appendectomy, continuous perioperative administration of intravenous lidocaine did not produce any adverse effects [ 26 ]. Consistent with our study, Fang et al supplied information supporting the use of the ketamine and lidocaine mixture which contributed to more stable vital signs, shorter onset and recovery time, elimination half-life prolonged, increased area under the curve, decreased plasma clearance, dosage and adverse effects [ 27 ]. Our results have shown that TIVA with lidoketofol decreased opioid consumption and shortened the extubating and recovery time.…”
Section: Discussionsupporting
confidence: 88%
“…In a retrospective analysis of data, in a limited number of pediatric patients undergoing general anesthesia for laparoscopic appendectomy, continuous perioperative administration of intravenous lidocaine did not produce any adverse effects [ 26 ]. Consistent with our study, Fang et al supplied information supporting the use of the ketamine and lidocaine mixture which contributed to more stable vital signs, shorter onset and recovery time, elimination half-life prolonged, increased area under the curve, decreased plasma clearance, dosage and adverse effects [ 27 ]. Our results have shown that TIVA with lidoketofol decreased opioid consumption and shortened the extubating and recovery time.…”
Section: Discussionsupporting
confidence: 88%
“…Similarly, Fang and cols. demonstrated a transaminase increase in pediatric patients sedated with ketamine (Fang et al, 2019). Whether or not the grafted FATLH may play a role in AST increase should be determined in future works.…”
Section: Discussionmentioning
confidence: 95%
“…[ 18 ] Ketamine inhibits morphine metabolism to increase the duration of analgesia, thereby exercising its intrinsic anti-inflammatory effects. [ 19 ]…”
Section: Discussionmentioning
confidence: 99%